Shelter : Off the Grid in the Mostly Magnetic North - Stonich, Sarah, 1958- (Book collections on Project MUSE., 2017)
"In her search for land to call her own--among tall pines and on a lake--newly single mom Sarah Stonich seeks a sense of permanence, a legacy for her son, and a connection to her heritage. Along this way, Stonich recalls family lore, meets remarkable characters, considers another go at love, and, finally, builds a cabin. But when her precious patch of land is threatened, she discovers that family is no less treasured with or without a piece of earth"--Provided by publisher.